The complete guide to decks : featuring the latest tools, skills, designs, materials + codes. (Cools Springs Press, an imprint of The Quarto Group, 2022)
Be inspired by new design and follow the latest codes as you custom build the deck of your dreams. Architecture, building codes, and design are not static; they change constantly. That's why there's a new edition of the best-selling BLACK+DECKER The Complete Guide to Decks, incorporating updates to national building codes, as well as new developments in building materials and design. Calling attention to composite deckboards and railings, as well as other PVC products made from recycled plastic, the new materials systems featured in this book are environmentally friendly, easy to work with, rot resistant, and very low maintenance. Whether you opt for manufactured deck products or wood, the success of your project depends upon a sturdy deck undercarriage. Accomplishing this isn't difficult, but building the framework requires that you have the latest information on building codes. In recent years, these codes have changed significantly, affecting everything from post diameter to allowable joist hangers to railing height and even the size of concrete footings. BLACK+DECKER The Complete Guide to Decks Updated 7th Edition is the only DIY deck book that's fully updated to conform to the latest codes. BLACK+DECKER The Complete Guide to Decks Updated 7th Edition offers complete step-by-step photos and instructions, so even homeowners with limited DIY experience are assured of a deck that meets their needs. So, don't wait any longer; build the deck of your dreams and start enjoying it!